Hak Menunaikan Ibadah bagi Buruh di Kota Gerbang Salam Pamekasan (Tinjauan Hukum Islam dan Undang-undang ketenagakerjaan) - Moch Cholid Wardi (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2020)
This research is trying to delve how the company or the employer put their laborers as human beings who at least pays attention on the three aspects of the employee’s right; they are recognition, appreciation and worship. In one side, it cannot be denied that the laborers need the appropriate management, facilities, and salary, but in another side, the employer needs to pay more attention on their needs as human being such as the need to do worship as they believe. There has been an interesting phenomenon about doing the worship for laborers happened in Pamekasan, and it becomes the focus of this research. It is how the laborers’ reality deals with the rights to do worship and how is the review of it from the Islamic law and the Labors law’s perspectives. Pamekasan with its jargon “Gerbang Salam” should have had a significant role in treating the laborers well deals with worship because theoretically it is legalized by the syara’ (Islamic law) and the constitution. This research used qualitative approach with developmental research kind. The result shows that there are some different regulations between one employer to another employers in applying the rights to do worship for the laborers. While from islam's prespective, this reality does not ban the laborers' right to do worship so that it can be categorized as maslahah hajiyah. It is in line with the Labor laws which does not forbit the laborers to do worship. All laborers are given such enough time to do worship although it may be different on it's length in some places because there is no exact regulation on the length of time to do worship in Pamekasan.